2021
DOI: 10.21203/rs.3.rs-757279/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

CBFA2T3-GLIS2 oncogenic fusion is sufficient for leukemic transformation

Abstract: Fusion oncoproteins are the initiating event in AML pathogenesis, although they are thought to require additional cooperating mutations for leukemic transformation. CBFA2T3-GLIS2 (C/G) fusion occurs exclusively in infants and is associated with highly aggressive disease1-4. Here we report that lentiviral transduction of C/G fusion is sufficient to induce malignant transformation of human cord blood hematopoietic stem and progenitor cells (CB HSPCs) that fully recapitulates C/G AML. Engineered CB HSPCs co-cultu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“… 7 We have previously demonstrated cell surface expression of FOLR1 in primary CBF/GLIS patient samples. 8 In addition, we also showed that cord blood cells that were transduced with a CBF/GLIS expression construct acquired high levels of FOLR1 expression, suggesting that FOLR1 expression is induced by the CBF/GLIS fusion oncoprotein. 8 Thus, FOLR1 may provide a promising and specific antigen target for CBF/GLIS AML.…”
mentioning
confidence: 57%
See 3 more Smart Citations
“… 7 We have previously demonstrated cell surface expression of FOLR1 in primary CBF/GLIS patient samples. 8 In addition, we also showed that cord blood cells that were transduced with a CBF/GLIS expression construct acquired high levels of FOLR1 expression, suggesting that FOLR1 expression is induced by the CBF/GLIS fusion oncoprotein. 8 Thus, FOLR1 may provide a promising and specific antigen target for CBF/GLIS AML.…”
mentioning
confidence: 57%
“… 8 In addition, we also showed that cord blood cells that were transduced with a CBF/GLIS expression construct acquired high levels of FOLR1 expression, suggesting that FOLR1 expression is induced by the CBF/GLIS fusion oncoprotein. 8 Thus, FOLR1 may provide a promising and specific antigen target for CBF/GLIS AML. Here, we present preclinical studies on the efficacy of STRO-002, a FOLR1-directed antibody-drug conjugate (ADC), developed by Sutro Biopharma for solid malignancies, 9 against CBF/GLIS AML.…”
mentioning
confidence: 57%
See 2 more Smart Citations
“…Upregulated molecules or pathways Downregulated molecules or pathways CBFA2T3::GLIS2 pathways: Hippo/TNF, TGFβ/BMP, Hedgehog, ECM-receptor interaction, Super Enhancers (Smith et al, 2020;Benbarche et al, 2022) molecules: cell-adhesion and cell-surface markers (e.g., CD56, CD44, ITGA2); RTKs (e.g., ROR1, MET, NTRK1); TAM family kinases (e.g., TYRO3, AXL); others (e.g., GLIS2, BMP2, HHIP, PTCH1, DHH, GLI1, RAB23, WNT9A, WNT11, ERG, DNMT3B, SLITRK5, KIT, PDGFRA, FOLR1) (Smith et al, 2020;Benbarche et al, 2022;Le et al, 2022) molecules: CD38, CD45, HLA-DRA, HLA-DRB1, HLA-DRB5, HLA-DRB6, CASP1, TRAIL-R2, GLIPR1, PER2, GATA1 (Smith et al, 2020) miRNAs : miR-203a-3p, miR-452-3p, miR-452-5p, miR-135a-3p, miR-5683, miR-224-5p, miR-224-3p, miR-6507-5p, miR-130a-3p, miR-181b-5p (Smith et al, 2020) miRNAs : miR-6503-5p, miR-196b-3p, miR-196b-5p, miR-133a-3p, and miR-5584-5p (Smith et al, 2020) KMT2Ar pathway: CDK6 (Placke et al, 2014;Schmoellerl et al, 2020) molecules: HOX cluster and others, such as HOXA9, MEIS1, S100A9, S100A8 (de Rooij et al, 2017;Milan et al, 2022) molecules: associated with stem cell phenotype, including CD34, GPR56, MN1 (de Rooij et al, 2017) (Milan et al, 2022) NUP98::KDM5A pathways: JAK-STAT, CDK6 (Cardin et al, 2019;Schmoellerl et al, 2020) pathways: Myc (Noort et al, 2021) molecules: HOXA cluster, HOXB cluster, MEIS1, MEIS2, E2F targets, FLT3 targets, STAT5 targets, NF1 targets, NOTCH1 targets, NEO1, MPIG6B, SELP (de Rooij et al, 2017;Cardin et al, 2019;Noort et al, 2021) molecules: RB1 (compared to all AMKL), TP53 Frontiers in Cell and Developmental Biology frontiersin.org along the granulocytic-monocytic lineages at the expense of erythroid-megakaryocytic differentiation (Chyla et al, 2008). GLIS2 is a member of the GLIS subfamily of Kru€ppel-like zinc finger transcription factors closely related to the GLI and ZIC subfamilies (Scoville et al, 2017).…”
Section: Molecular Subgroupmentioning
confidence: 99%